Comparison of knowledge, attitude, practices, and psychological impact of COVID-19 among the urban and rural population of Bangalore, Karnataka - Nuthan Bhat; Hiba Salam; Sushma Javvaji; Ananya Chakraborty (Wolters Kluwer Medknow Publications, 2022)
Context and Objectives: There is a strong urban-rural divide in India in terms of education, economic status, and availability of health care. This became more prominent during the COVID-19 pandemic. Hence, the government emphasized on preventive aspects, especially in terms of safety practices. With this context, this study sought to evaluate and compare the knowledge, attitudes, practices, and psychological impact of COVID-19 among the urban and rural population of Bangalore to study the differential effects on both communities. Materials and Methods: An online questionnaire was distributed to 142 participants between December 1 and 31, 2020. The goal was to receive responses from both urban and rural population of Bangalore. Informed consent was taken from all participants. The response scores were tabulated and analyzed using statistical software. Results and Conclusion: A total of 138 responses were evaluated. In comparison to the urban population, there was a statistically significant link between inferior education and occupation in the rural population. (P 0.001). There was a statistically significant difference between rural and urban respondents in terms of knowledge (P 0.001) and attitude (P 0.05). The rural population's COVID-19 practices and the psychological impact were shown to be worse, but this was not statistically significant. A holistic approach is required to increase the rural population's knowledge and practices to integrate them with the rest of the country and combat the COVID-19 pandemic more effectively.